EFEKTIFITAS BIMBINGAN KELOMPOK DENGAN TEKNIK REFRAMING UNTUK MENINGKATKAN KEPEKAAN SOSIAL SISWA KELAS XI SMAIT AL- GHAZALI JEMBER - Bil Qisthi, Qoimah; Hikmatul Maghfiroh, Nasruliyah; Ulwiyah, Imaratul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to investigate the effectiveness of group guidance using the reframing technique to enhance social sensitivity among eleventh-grade students at SMAIT Al Ghazali. The method employed is a pre-experimental design with a one-group pre-test and post-test framework. The population consisted of 23 eleventh-grade students, with a sample size of 6 students. Data analysis was conducted using the Wilcoxon test to compare pre-test and post-test scores. The results showed that the average pre-test score increased from 55 to 95.33 in the final post-test. The Wilcoxon test yielded an Asymp. Sig (2-tailed) value of 0.028, which is less than 0.05, indicating that the hypothesis is accepted. In conclusion, group guidance using the reframing technique effectively increases the social sensitivity of eleventh-grade students at SMAIT Al Ghazali in Jember.